2021
DOI: 10.3390/ijms222212274
|View full text |Cite
|
Sign up to set email alerts
|

The GTPase Arf1 Is a Determinant of Yeast Vps13 Localization to the Golgi Apparatus

Abstract: VPS13 proteins are evolutionarily conserved. Mutations in the four human genes (VPS13A-D) encoding VPS13A-D proteins are linked to developmental or neurodegenerative diseases. The relationship between the specific localization of individual VPS13 proteins, their molecular functions, and the pathology of these diseases is unknown. Here we used a yeast model to establish the determinants of Vps13′s interaction with the membranes of Golgi apparatus. We analyzed the different phenotypes of the arf1-3 arf2Δ vps13∆ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 89 publications
(135 reference statements)
0
30
0
Order By: Relevance
“…S. cerevisiae Vps13 localizes to multiple MCSs, including the Nuclear Vacuolar Junction (NVJ), the vacuole-mitochondria patch (vCLAMP) and endosome-mitochondrial contact sites ( Dziurdzik and Conibear, 2021 ). In addition, S. cerevisiae Vps13 localizes to prospore membranes ( Park and Neiman, 2012 ), the Golgi apparatus ( Kolakowski et al, 2021 ) and peroxisomes ( John Peter et al, 2017 ). Most likely H. polymorpha Vps13 also localizes to multiple organelles.…”
Section: Discussionmentioning
confidence: 99%
“…S. cerevisiae Vps13 localizes to multiple MCSs, including the Nuclear Vacuolar Junction (NVJ), the vacuole-mitochondria patch (vCLAMP) and endosome-mitochondrial contact sites ( Dziurdzik and Conibear, 2021 ). In addition, S. cerevisiae Vps13 localizes to prospore membranes ( Park and Neiman, 2012 ), the Golgi apparatus ( Kolakowski et al, 2021 ) and peroxisomes ( John Peter et al, 2017 ). Most likely H. polymorpha Vps13 also localizes to multiple organelles.…”
Section: Discussionmentioning
confidence: 99%
“…This region is followed by a PH-like domain which generally interacts with phosphoinositides (Fidler et al, 2016). Extensively studied in yeast and human VPS13A, this PH-like domain was shown to bind Arf1 GTPase and bis and tris -phosphorylated phosphoinositides (Kolakowski et al, 2021). As our in silico approach and protein-membrane simulations did not predict the PH-like domains to exhibit significant hydrophobicity nor to be positively charged and to disturb lipid surfaces, suggesting membrane targeting interactions only (Videos S1-S4).…”
Section: Discussionmentioning
confidence: 99%
“…We undertake an in silico approach to investigate possible mechanisms of the VPS13 lipid transfer function. An N-terminal hydrophobic groove was previously found to solubilise tens of lipid fatty acid moieties (Adlakha et al, 2022; Kolakowski et al, 2021; Kumar et al, 2018) and extends across the bulk length of the protein in the form of β-strand repeats and their laterally connected α-helices or unstructured peptides, giving rise to the recently named repeating β-groove (RBG) domain (Neuman et al, 2022). Recognition motifs and protein-binding domains decorate VPS13s along their lipid transferring channels, which span across intermembrane contact sites that may vary between ∼10-40 nm in distance (Cai et al, 2022; Neuman et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However it is becoming clear that Vps13 recruitment and function is more complex than this simple paradigm. For example, a recent report in yeast showed that the Arf1 protein binds to the PH domain of Vps13 to recruit Vps13 to the Golgi (Kolakowski et al, 2021).…”
Section: Discussionmentioning
confidence: 99%